A Novel Design of Slotted Waveguide Phased Array Antenna - Elhefnawy, M.; Al-Hadi, A. A. (Advanced Electromagnetics, 2019)
A novel design of phased array antenna based on a Slotted Waveguide Antenna Array (SWAA) is introduced in this paper. The CST Microwave Studio simulation results show that the S‒parameters, the gain, the axial ratio, and the beamwidth of the proposed phased array antenna are affected by the value of the progressive phase shift. The simulated results of the proposed phased array antenna at different values of progressive phase demonstrate that the S‒parameters for almost all ports are less than ‒10 dB over at least 2% bandwidth, the simulated phased array antenna gain is above 17 dB in the frequency range from 9.5 GHz to 9.7 GHz, the range of frequencies over which the simulated Axial Ratio (AR) is below 3 dB is not fixed and varied according to the selected progressive phase, the simulated beamwidth can be 6.5˚ or narrower based on the value of the progressive phase shift.